2001
DOI: 10.1063/1.1355656
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman spectroscopy in the dissociative A band of nitrosyl chloride

Abstract: Ab initio potential energy surfaces, total absorption cross sections, and product quantum state distributions for the low-lying electronic states of N 2 O Resonance Raman spectra measured for ClNO photoexcited at 212.5, 219, and 222 nm produce evidence that the strong transition at the vacuum ultraviolet end of the merged A band system dominates to wavelengths as long as 222 nm. The spectral resolution is sufficient to enable definitive assignments of excited vibrational levels in the ground electronic state, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 50 publications
4
21
0
Order By: Relevance
“…30 For the bound levels we investigate, it is found that eigenvalues and eigenvectors are all converged tobetter than 0.0001 cm −1 using the intervals 0.8 Å ഛ r ഛ 1.6 Å, 1.5 Å ഛ R ഛ 3.5 Å, and −1 ഛ z ഛ 0 with inner scaling function bases of sizes 124, 200, and 124, respectively. 30 For the bound levels we investigate, it is found that eigenvalues and eigenvectors are all converged tobetter than 0.0001 cm −1 using the intervals 0.8 Å ഛ r ഛ 1.6 Å, 1.5 Å ഛ R ഛ 3.5 Å, and −1 ഛ z ഛ 0 with inner scaling function bases of sizes 124, 200, and 124, respectively.…”
Section: Curvilinear 3d Examplementioning
confidence: 92%
See 2 more Smart Citations
“…30 For the bound levels we investigate, it is found that eigenvalues and eigenvectors are all converged tobetter than 0.0001 cm −1 using the intervals 0.8 Å ഛ r ഛ 1.6 Å, 1.5 Å ഛ R ഛ 3.5 Å, and −1 ഛ z ഛ 0 with inner scaling function bases of sizes 124, 200, and 124, respectively. 30 For the bound levels we investigate, it is found that eigenvalues and eigenvectors are all converged tobetter than 0.0001 cm −1 using the intervals 0.8 Å ഛ r ഛ 1.6 Å, 1.5 Å ഛ R ഛ 3.5 Å, and −1 ഛ z ഛ 0 with inner scaling function bases of sizes 124, 200, and 124, respectively.…”
Section: Curvilinear 3d Examplementioning
confidence: 92%
“…[37][38][39][40] One appropriate example is given by nitrosyl chloride, for which dissociative resonance Raman experiments by Mackey et al 30 have extended the number of observed vibrational transitions to a total of 27 reaching up to 7000 cm −1 above the ground state. It is then important to be able to construct and evaluate vibrational models in one set of curvilinear coordinates or another, for which one may again use SCF-CI methods.…”
Section: Curvilinear 3d Examplementioning
confidence: 99%
See 1 more Smart Citation
“…The equilibrium values ͑r e , R e , z e ͒ and linear and nonlinear parameters are given in Mackey et al 28 Wavelet bases, despite having been constructed originally for Cartesian problems, can be used for each of the coordinates. The equilibrium values ͑r e , R e , z e ͒ and linear and nonlinear parameters are given in Mackey et al 28 Wavelet bases, despite having been constructed originally for Cartesian problems, can be used for each of the coordinates.…”
Section: ͑36͒mentioning
confidence: 99%
“…Recently, an extensive study was carried out using the resonance Raman experiment. 12 On the theoretical ground, many vibrational analyses have been performed. [13][14][15][16][17][18] Particularly, ab initio/empirical potential energy function study by Botschwina, Haertner, and Sawodney 13 is notable.…”
Section: Introductionmentioning
confidence: 99%